The comparison of interstitial relative humidity and temperatures of hermetic and polypropylene bag for wheat grain storage under different agro-climatic conditions of rice-wheat ecosystem of Pakistan: Effect on seed quality and protection against insect pests. (March 2022) - Rizwan, Muhammad; Atta, Bilal; Ali, Muhammad Yasir; Ashraf, Ijaz; Arshad, Muhammad; Tahir, Muhammad; Rizwan, Misbah; Sabir, Arshed Makhdoom; Shehzadi, Neelum; Khalid, Usama Bin; Iqbal, Shawaiz; Pan, Ming-Zhen; et al.
Abstract: Wheat Triticum aestivum (L.) is an important staple food in Pakistan. However, post-harvest losses either quantitatively (weight loss, commercial loss) or qualitatively (changed appearance and lower nutritional value) by various stored grains insect pests, and environmental conditions are major concern. This study was aimed to evaluate the efficacy of hermetic and polypropylene bags in protection against insect pests and maintaining grain quality under different environmental conditions. Results showed that grain moisture fluctuated in polypropylene bags with variations in relative humidity in the environment, while in the hermetic bag it was decreased in all three sites. Relative humidity reduced in hermetic bags on all three sites and became constant within a week for the rest of the period while increased in polypropylene bags due to environmental humidity and insect infestation. However, a great variation in temperature fluctuation in both bags on all three sites was recorded. Germination remained unaffected in hermetic bags while a significant reduction (35%) occurred in polypropylene bags. Insects were unable to damage grains inside hermetic bags while grain weight loss (14.97–15.53%), damaged grains (27.43–30.93%), and reduced germination (26–27.5%) were recorded in polypropylene bags due to infestation of insect pests ( Tribolium castaneum (Herbst), and Sitophilus granarius L. and S. oryzae L). Moreover, no aflatoxins were recorded in both bags at all three sites. Our findings suggest that in Pakistan, it is technically feasible to control insect pests of storage by using hermetic storage bags. Highlights: Storage technology effects on grains damage by insect pests and adverse climate. Hermetic bag is the best storage material to reduce grain damage due to insect pests. Germination of seeds remains unaffected in hermetic bags. Polypropylene bags are not safer for long term storage of seeds.